Care Considerations in a Patient- and Family-Centered Medical Assistance in Dying Program. Issue 3 (July 2022) - Brown, Janine; Goodridge, Donna; Harrison, Averi; Kemp, Jordan; Thorpe, Lilian; Weiler, Robert
Objective: Medical Assistance in Dying (MAID) became legal in Canada in June 2016. As part of a project designed to improve end-of-life care for those requesting MAID, qualitative data from patients, families, and providers were used to assess opportunities to enhance patient-and family-centered care (PFCC) in this program.Methods: Thirty interviews were conducted with patients, families, and healthcare providers. Five patients who requested an assessment for MAID, 11 family members, and 14 healthcare providers were interviewed about their experiences in 2017. Comparative coding and thematic analysis were completed with the support of NVivo12.Results: Emotional PFCC considerations included: exploring and validating the emotional journey, navigating the uncertain, judgmental experiences, and the emotional impact on families and the care team. Physical PFCC considerations included: sensitivity in eligibility assessments, weaving in interdisciplinary care, provision of anticipatory guidance, and death location. Spiritual PFCC considerations included: honoring choice, listening to life stories, supporting spiritual needs, and acknowledging loss. Relational PFCC considerations included: defining the circle of support, supporting the circle, and relational investments.Conclusion: Fundamental to a PFCC MAID program, practitioners must be afforded time to provide holistic care. Program-related suggestions include incorporating interdisciplinary care early, and throughout the illness trajectory, consistency in care providers, appropriate anticipatory guidance, and bereavement supports for family, and dedicate space for MAID provisions. Patients and families must be included in the ongoing development and re-evaluation of MAID programs to ensure continued focus on quality end-of-life care.